Acta Veterinaria Scandinavica reviewer acknowledgement 2013 - Agerholm, Jørgen S (BioMed Central, 2014)
CONTRIBUTING REVIEWERS: The Acta Veterinaria Scandinavica editorial team would like to thank the following colleagues who contributed to peer review for the journal in 2013.